Evaluasi Pasca Pelatihan pada Pelatihan Pengelolaan Sistem Informasi Keluarga di Badan Kependudukan dan Keluarga Berencana Nasional Yogyakarta - Vina Ulfiya Fadlila; Anggraeni Wulandari (Pancanaka, 2021)
Sistem Informasi Keluarga (SIGA) management training needs to be evaluated. Evaluation is another word for assessment. Evaluation is important to collect data and determine the extent to which educational goals have been achieved. The evaluation model used is the Kirkpatrick level 3 and 4 model. The data were obtained through questionnaires, observations, interviews, and documentation instruments and were analyzed using quantitative descriptive analysis techniques. Interviews and questionnaires were conducted to the trainees, the trainees' colleagues, and the trainees' superiors. Evaluation at level 3 is categorized into three aspects, namely aspects of attitude, knowledge, and skills. The result of level 3 evaluation is that in the aspect of the attitude of the participants before and after the training there is an increase of 18.39%. Aspects of knowledge of participants before and after the training there was an increase of 16.02%. Meanwhile, the skill aspect of the participants before and after the training increased by 19.69%. At level 4, namely impact, the training participants showed that the training held was successful and achieved its goals well, such as changes in the institution in a positive direction and changes in improving the performance of training participants supported by improving attitudes so as to obtain optimal work quality.